Perceptual experience and epistemic support - Falguera, José Luís; Peleteiro, Santiago (Revista de Filosofía, 2014)
In this paper we analyze the problem of how our perceptual experiences give epistemic support to our beliefs. We begin with some considerations formulated by Fodor, but revise them in some respects. We consider, in particular, his recent proposal for the existence of non-conceptual representations in perceptual information processing. Our aim is to vindicate, against the arguments raised by some representatives of so-called ‘perceptual conceptualism’, a normative role for perceptual experiences insofar as they are conceived as representations with non-conceptual content.